The Tekenu and ancient Egyptian funerary ritual - West, Glennise, (Archaeopress Egyptology ;, 2019)
Attested from the Fifth Dynasty until, and including, the Saite Period, the Tekenu is a puzzling icon depicted within funerary scenes in the tombs of some ancient Egyptian nobles. In this work four distinct types of Tekenu are identified and classified and then a Corpus Catalogue is formed.